KARAKTERISTIK PENDERITA SIROSIS HATI YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABET MEDAN TAHUN 2012-2014 - esta hayati sitompul; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Liver cirrhosis is one of the diseases that can be found throughout the countries. According to WHO (2008), Liver cirrhosis in the world was ranked as eighth leading caused of death with the death rate of 664.755 casses. In USA (2010), cronic liver disease and Liver cirrhosis had caused the number of death as many as 31.903. In Indonesian, the prevalence of Liver cirrhosis haven’t been found yet. The CFR of Liver cirrhosis in Santa Elisabet’s Hospital Medan in 2012-2014 was 10,6%. The aim of this study is to know the characteristics of patient with Liver cirrhosis which hospitalized at Santa Elisabet’s hospital Medan in 2012-2014. This study is adopted descriptive research with Case Series design. The population were 158 patients, with sample were 113 patients. Liver cirrhosis Patient with the highest proportions in the age group 50-59 years old (31,9%), male (62,8%), Batak tribe (79,6%), Protestant (69,9%), civil employee/retired civil employee (23%), living on suburb (71,7%), primary complaint with painful right top belly while visiting (38,1%), history of previous illness is Hepatitis B (17,7%), complicated status exiting (76,1%), ascites type of complication (57%), self cost source (93,8%), the length of average treatment 7,26 days, and coming home condition was by the willing of the patient (73,5%). There is a significant differences between the age poportion based on the type of complication (p=0,006), there is no significant differences between sex proportion based on the history of previous illness (p=0,666), there is no significant differences between the type of complication proportion based on the history of previous illness (p=0,339), there is no significant differences between sex proportion based on type of complication (p=0,347), there is no significant proportion difference between length of average treatment based on the type of complication (0,075), there is no significant difference between the type of complication based on condition while coming home (p=0,094). Recommended to the staff of the  Santa Elisabet’s hospital Medan to give conseling to the family of the patients  about the real condition of the patients, the risky factors of Liver cirrhosis and the preventions of Liver cirrhosis that can be done. Key Words : Liver Cirrhosis, Characteristics of Patient